Molecular Characterization and Feeding-Associated Expression Dynamics of the Period Gene Family in Channel Catfish (Ictalurus punctatus) - Hongyan Liu; Shiyong Zhang; Xiaohui Chen; Minghua Wang; Liqiang Zhong; Yongqiang Duan; Bingjie Xie; Luyu Tang; Yi Cheng (Current Issues in Molecular Biology, 2025)
Rhythms, regulated by core clock genes like the period (per) gene family, are crucial for maintaining physiological processes in animals. In teleost fish, including channel catfish (Ictalurus punctatus), these genes have evolved distinct functions. However, the evolutionary characteristics and functional roles of period genes, particularly in response to environmental cues such as feeding, remain unclear. This study aimed to investigate the evolutionary divergence and functional specialization of the period gene family in channel catfish, with a focus on feeding-induced rhythmicity. Four period genes, Ipper1b, Ipper2, Ipper2l, and Ipper3, were identified in channel catfish. Phylogenetic analysis revealed distinct evolutionary paths for these genes, with Ipper2l forming a separate clade from Ipper2. Tissue-specific expression analysis showed differential expression of period genes across tissues, with Ipper1b exhibiting the highest expression in the intestine and Ipper2 being predominantly expressed in the liver. Statistical analysis confirmed significant differences in the expression levels between tissues (p < 0.05), supporting the tissue-specific roles of these genes. Notably, under strict feeding schedules, we observed significant modulation of rhythmic expression in both the brain and liver, with a notable shift in the peak expression times and amplitude changes aligned with the feeding time. These results suggest that feeding serves as a critical Zeitgeber, entraining circadian rhythms in key tissues and potentially enhancing metabolic efficiency. These results demonstrated that feeding schedules play a key role in modulating circadian gene expression in channel catfish. This study provides insights into the evolutionary divergence and functional roles of the period gene family in channel catfish, showing how feeding schedules modulate circadian gene expression in the brain and liver. These findings have potential applications in optimizing feeding strategies for improving fish health and growth in aquaculture.